Challenging school reform from below: is leadership the missing link in mobilization theory? - Stevenson, Howard (Taylor & Francis, 2016)
This article presents research relating to the experiences of union and community-based campaigns that have sought to challenge the establishment of academy and free schools in England. Such schools are removed from local government control and are seen as a defining element of the neoliberal restructuring of public education. The research draws on social-movement literature, and particularly mobilization theory, to better understand the dynamics of such campaigns and the contexts in which they can either thrive or wither. In the article, I argue that mobilization theory provides a useful framework for such analysis but that it fails to adequately reflect the importance of individual agency and the role of leadership at a local level. Leadership of such campaigns is often assumed by individuals reluctantly, and often defies traditional descriptions of “leadership,” but must be recognized if mobilization theory is to avoid being overly deterministic.